Addressing Crisis in the Educational System for A Self-Driven Curriculum Development - Mallillin, Leovigildo Lito (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
The study aims to analyze addressing crises for the educational system and self-driven curriculum development as trends in the quality of teaching and learning. Phenomenological qualitative research methods are employed in the study. It analyzes the critical problem needs to be addressed in curriculum designing for the educational system alignment evolvement of the educational needs among students as centers of learning, educational crisis balance standard flexibility in a self-driven curriculum system, resource limitations address the needs of the self-driven curriculum in the educational system for the learners, and hindrances on the success of teacher preparedness and training in minimizing the crisis for the self-driven curriculum in the educational system. The study consisted of Fifty (50) participants only.             Results show that self-driven curriculum determines the educational system and quality of learning through skills and knowledge, show that evolvement of educational needs aligns curriculum in the rapid work change on outdated content to meet the modern teaching workforce requirements, show that balance standard flexibility ensures consistency on the educational curriculum to cater diverse needs and lack of flexibility, show that resource limitation implements and develops curriculum requirements for high quality technology, teaching materials, and professional development, and show that teacher preparedness and training in the curriculum delivery due to lack of professional development alignment in the curriculum for self-driven system.